Patrons of Faith : the Catholic Nobility in Utrecht and Guelders, C. 1580-1702. - Geraerts, Jaap (Catholic Christendom, 1300-1700 Ser., 2018)
Patrons of the Old Faith is the first full-length study on the Catholic nobility in the Dutch Republic. Based on a detailed prosopographical analysis and through the examination of their marriage strategies, interaction with Protestants, religiosity and contributions to the Holland Mission, Jaap Geraerts shows how the behaviour of the Catholic nobility was highly distinctive and differed from their co-religionists and Protestant peers as it was influenced by a specific set of noble and Catholic values. Due to the synthesis of their noble and confessional identities, the Dutch Catholic nobility in Utrecht and Guelders acted as patrons of their faith and were instrumental for the survival of Catholicism in the Dutch Republic.